The predict - observe - explain instruction coupled with reflective journal writing for teaching electricity and magnetism: a quasi - experimental study with grade 10 students - Akkılık, Erhan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
The main purpose of this quasi-experimental study was to explore the effectiveness of ―Predict-Observe-Explain instruction coupled with Reflective Journal Writing‖ (POE-RJW) over POE instruction or Traditional Instruction (TI) in terms of improving Grade 10 students‘ conceptual understandings of electricity and magnetism. The subsequent goal of the study was to investigate the effectiveness of the POE-RJW instruction over the POE instruction and the TI in terms of increasing students‘ motivation to learning physics. A total of 135 male Grade 10 students from a high school located in Istanbul were involved in the study. The two of pre-existing classes of the school were randomly assigned as the POE-RJW group, including 39 students; three classes were randomly assigned as the POE group, including 59 students, and the two of them were assigned as the TI group, including 37 students. Three essential data sources were used in the current study: (1) Electricity and Magnetism Conceptual Test (EMCT), which comprised of 20 two-tier questions to assess students‘ conceptual understandings of electricity and magnetism. (2) Physics Motivation Questionnaire (PMQ) which included 22 Likert-type items to assess students‘ motivation to learning physics, and (3) Journal Writing Survey (JWS) to identify the opinions and perceptions of students regarding the act of journal writing. Both EMCT and PMQ were administered before and after a ten-week instruction in three different groups. Quantitative analysis was conducted for EMCT and PMQ. Before the instructions all three groups showed similar conceptual understanding about the concepts of electricity and magnetism, and motivation towards learning physics. After the instructions, the POE-RJW group outperformed the POE and the TI group in terms of understanding the concepts of electricity and magnetism, and motivation to learning physics. The findings of the study showed that ―Predict-Observe-Explain instruction coupled with Reflective Journal Writing‖ (POE-RJW) can be used to promote students' conceptual understanding in science and also to increase their motivation towards learning physics.
Keywords: Reflective teaching.